First reports of the soft scale insect genera Leptopulvinaria Kanda and Pulvinarisca Borchsenius (Hemiptera: Coccomorpha: Coccidae) from India, with descriptions of two new species and identification keys - Joshi, Sunil; Dubey, Anil Kumar; Gupta, Ankita; Sushil, Satya Nand (Zootaxa, 2025)
Two genera of soft scale insects (Hemiptera: Coccomorpha: Coccidae), Leptopulvinaria Kanda and Pulvinarisca Borchsenius are reported from India for the first time, each with a new species, namely Leptopulvinaria harishi Joshi, sp. nov. and Pulvinarisca greeni Joshi & Dubey, sp. nov., which are described and illustrated. The new species of Leptopulvinaria is most similar morphologically to L. sapinda He, Ha & Wu, while the new species of Pulvinarisca is morphologically close to P. serpentina (Balachowsky). Keys are provided to the adult females of all the species in both genera. An ant, Oecophylla smaragdina (Fabricius) (Hymenoptera: Formicidae) was found attending both the scale insects. Two hymenopterous parasitoids, Encyrtus noyesi Singh (Encyrtidae) and Coccophagus sudhiri Hayat (Aphelinidae) were recorded from L. harishi.